2022
DOI: 10.1038/s41533-022-00315-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient uptake and outcomes following pharmacist-initiated referrals to general practitioners for asthma review

Abstract: Uptake and outcomes of pharmacist-initiated general practitioner (GP) referrals for patients with poorly controlled asthma were investigated. Pharmacists referred at-risk patients for GP assessment. Patients were categorized as action takers (consulted their GP on pharmacist’s advice) or action avoiders (did not action the referral). Patient clinical data were compared to explore predictors of uptake and association with health outcomes. In total, 58% of patients (n = 148) received a GP referral, of whom 78% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…For example, in a study conducted on patients with maternal asthma, patient education, including inhalation instruction and the use of an electronic spirometer by a pharmacist, resulted in a significant reduction in ACQ scores in the intervention group compared with a control group 68 . Similarly, an Australian study of a pharmacist-led pharmacy asthma service intervention for patients with poorly controlled asthma that addressed adherence, inhalation techniques, and allergic rhinitis showed that asthma treatment was reviewed in approximately half of the patients who consulted a general practitioner based on the pharmacist’s suggestion 69 . Other studies have found that nurse-led interventions by so-called “asthma nurses” increased knowledge of inhaled medications 70 and decreased the rate of acute exacerbations 71 .…”
Section: Overcoming Clinical Inertia In Asthmamentioning
confidence: 99%
“…For example, in a study conducted on patients with maternal asthma, patient education, including inhalation instruction and the use of an electronic spirometer by a pharmacist, resulted in a significant reduction in ACQ scores in the intervention group compared with a control group 68 . Similarly, an Australian study of a pharmacist-led pharmacy asthma service intervention for patients with poorly controlled asthma that addressed adherence, inhalation techniques, and allergic rhinitis showed that asthma treatment was reviewed in approximately half of the patients who consulted a general practitioner based on the pharmacist’s suggestion 69 . Other studies have found that nurse-led interventions by so-called “asthma nurses” increased knowledge of inhaled medications 70 and decreased the rate of acute exacerbations 71 .…”
Section: Overcoming Clinical Inertia In Asthmamentioning
confidence: 99%